Advances in herbal and synthetic transferosomes: routes, formulation challenges and comparative performance - Dattatreya; Vijaykumar Meti; Sai Teja K; Parwati V Naikar (Journal of Applied Pharmaceutical Research, 2026)
Background: Transferosomes are ultra-deformable vesicular carriers widely investigated for enhancing drug delivery across biological barriers. Both herbal and synthetic transferosomes have gained attention for improving permeability, bioavailability, and therapeutic efficacy. However, a comparative understanding of their formulation strategies, therapeutic performance, and associated challenges remains limited. Methodology: A systematic literature review was conducted to compare herbal and synthetic transferosomes. A total of 100 research and review articles were analyzed, including 50 studies each on herbal and synthetic formulations. Data were categorized based on formulation benefits, challenges, routes of administration, and dosage forms, and analyzed to determine the frequency of these parameters. Results and Discussion: Synthetic transferosomes exhibited higher permeability (30%), stability (18%), solubility (10%), and vesicle deformability (13%) due to their defined composition and controlled formulation. However, scalability 27%, vesicle size control, and encapsulation efficiency remained major challenges. Herbal transferosomes demonstrated improved bioavailability (20%) and drug delivery efficiency (18%), likely due to the synergistic effects of phytoconstituents. Nevertheless, they showed greater extract variability (28%) and formulation instability (18%). Transdermal delivery was the predominant route, accounting for 80% of herbal and 65% of synthetic formulations, with gels being the most common dosage form. Conclusion: Synthetic transferosomes provide better formulation control and reproducibility, whereas herbal systems offer enhanced therapeutic potential. Optimization of formulation parameters and stability is essential to improve the translational applicability of both systems.